Bronchial hyperreactivity and spirometric impairment in patients with allergic rhinitis - Cirillo, I.; Vizzaccaro, A.; Tosca, M.A.; Negrini, S.; Negrini, A.C.; Marseglia, G.; Ciprandi, G. (Monaldi Archives for Chest Disease, 2005)
Background: The Link between allergic rhinitis and asthma is well known. Bronchial hyperreactivity (BHR) may be present in rhinitics. The present study is aimed at evaluating a large group of subjects suffering from allergic rhinitis alone to investigate the presence of spirometric impairment and BHR both during and outside the pollen season. Methods: 360 rhinitics (subdivided in 3 groups: seasonal, SAR, perennial, PAR, and polysensitized, PolysR) were investigated by spirometry and methacholine challenge. Results: There was a significant seasonal difference concerning the number of rhinitics with impaired FEV1 (p<0.01 for SAR, p<0.02 for PAR, and p<0.03 for PolysR) and FEF25-75 (p<0.05 for SAR, p<0.03 for PAR, and p<0.05 for PolysR) as well as with BHR (p<0.05 for SAR and p<0.03 for PAR). Conclusions: This study evidences that an impairment of spirometric parameters and BHR may be observed in patients with allergic rhinitis alone. Thus, careful evaluation of lower airways should be performed in patients with allergic rhinitis alone.